The Evaluation of Web-based English Language Learning Media for Nursing Students - Halim, Abdul; Johar Latipah, Asslia (International Journal of Engineering and Technology, 2019)
This paper was aimed at evaluating a web-based English language learning media collaboratively developed by the researchers, by using CMS, following the emerging notion about industrial revolution 4.0 and the internet of things, which was sounded by the government. This study employed case study design. This study involved the experts of both material expert in language teaching and IT experts as the evaluator from the perspective of their expertise. In addition, it also involved 50 students of the 4th semester from the nursing department of Universitas Muhammadiyah Kalimantan Timur as the evaluating users of the websites. The data was analyzed descriptively and the data collected from surveying the students was analyzed by using SPSS descriptive quantitative. The result showed that the web which had been developed as material for language learning is feasible after getting valuable feedback from the experts and the students as the user. It can be concluded that the web-based language learning media developed by utilizing CMS was very useful, easy, and practical for both the teacher and the students.Â